Konektivitas ASEAN : Sebagai Sebuah Pergeseran Paradigma Dalam Proses Integrasi ASEAN - Haiyyu Darman Moenir (Andalas Journal of International Studies (AJIS))
Establishment of ASEAN in the period 1967 to 2010, ASEAN as a regional organization undergone many changes, both in terms of the dynamics of the issues faced up to the stage of organizational structure. Globalization of trade liberalization resulting in movement of goods and services become limited. This encourages the re-realization of the ASEAN countries in order to restructure and integrate their economies in order to maintain their competitiveness, which in turn make ASEAN a more in-depth integration by establishing the ASEAN Economic Community (AEC) by 2015. Economic integration is expected to be used as a means to revitalize the economy of ASEAN. With the implementation of economic integration, it is hoped will be a driver of growth is faster than all the countries in ASEAN. Therefore, the connectivity becomes very important for ASEAN countries as one of the conditions necessary for ASEAN integration process that evolved into the ASEAN Community, and also ensure the centrality of ASEAN as a regional architecture that evolves dynamically. Connectivity plan for the year 2015 according to the plan will involve the physical connectivity, institutional connectivity, and connectivity of the individual.